Patterns of absence of compulsory age students : a retrospective study - Ioannakis, Irene (Curtin University, 1997)
This study focusses on the examination of the recorded absences of compulsory age students. The main purpose was to identify emergent patterns of school non-attendance, critical periods of absences and key factors within and beyond the school that might contribute to school non-attendance and the impact such non-attendance has on student achievement and perceptions of schooling.A review of literature on school non-attendance was undertaken and presented to highlight the number of factors that are often linked with non-attendance. As a result of the literature review a comprehensive list of factors for further investigation was distilled and a conceptual framework was developed. It was this conceptual framework, together with the research questions, that guided the research design and the subsequent collection and analysis of data.The research was undertaken in Perth, Western Australia utilising one State Government secondary school and five of its contributory (or feeder) primary schools. The research constituted a retrospective study spanning seven years (1989 to 1995 inclusive) incorporating the complete attendance records of 61 students.The first phase of the study involved the establishment of an empirical database developed from records compiled by the five feeder schools and the secondary school under study. Data derived from the schools were analysed to establish the patterns of non-attendance and trends.The second phase involved a series of case studies in which student perceptions on school non-attendance were investigated alongside the student's characteristics and attendance patterns in order to provide greater insight into key factors contributing to school non-attendance.The case studies not only provided greater insight into key factors contributing to school non-attendance but also the impact non-attendance had on the educational outcomes of the deemed 'at risk' students.Finally, the thesis provides a number of conclusions and action statements to all key stakeholders including the schools at the centre of this research, policy makers within the State Government Education Department, parents, and personnel from other schools within Western Australia, for future action and continuing research. There is a collective responsibility to ensure all students maximise their learning outcomes through the educational programs provided in the schooling system.The study also has the potential to provide a framework at both the national and international level as the outcomes of this research have potential significance for a number of interested organisations involved in providing educational and other programs for 'at risk' students.